Cross-border internet dispute resolution / Julia Hörnle. - Hörnle, Julia, 1970- (Cambridge University Press, 2009)
The internet has the potential to increase the number of cross-border disputes between a wide range of different users. For many internet disputes, the use of Online Dispute Resolution (ODR) becomes critical. ODR uses information technology (such as expert systems) and internet communication applications (such as webforms or web filing platforms) to resolve disputes outside the courts. Although ODR is a progeny of ADR, using some of the same processes such as mediation and arbitration, ODR is also different in that it adds new and transformative technology and processes. This book sets out the process standards with which ODR, and in particular online arbitration, should comply and shows how these standards can be implemented in the real world. It considers applicable law and enforcement, thus providing a blueprint of how online arbitration processes should be devised.